Relationship Between Managers Communication Skill and Staff Motivation in Modarres Hospital of Tehran - Seyed J Tabibi; AA Nasiripoor; Z Zahiri abyaneh (Tehran University of Medical Sciences, 2013)
Background:  It  is  a  long  time  that  the  matter  of  manager`s  Communication  skills  and  staff motivation  have  come  up  in  Iranian  hospitals.  This  study  determined  the  relationship  between manager`s communication skills and staff motivation to identify the present situation and provide managers with appropriate strategies to enhance the motivation level of employees in the Modares hospital. Materials and Methods: This study was conducted using a descriptive-correlative method. The statistical society consisted of 66 individuals including 11 top and mid-level managers and 55 of their affiliated staff which were selected using a clustered model from the medical and administration sections. Data were collected using a 3- part questionnaire. Demographic data were measured in the first part while communication skills and motivation were measured in the second and third parts separately. Manager`s communication skills were measured using the Ardeshirzadeh(2005) questionnaire while Mokhbery questionnaire (2008) was used to measure staff motivation.The data were analyzed by the SPSS software using statistical indicators, relative frequency, mean and standard deviation, nonparametric tests and Pearson correlation factor. Results: The average of the three dimensions of manager`s communication skills were (3.57± 0.57) for non-verbal skills, (3.24 ± 0.62) for the underlying communication skills and (3.23 ± 0.88) for verbal communication skills in a descending order while the average score of staff motivation was (2.57 ± 055). Meanwhile results from the Pearson correlation factor showed that there is only a significant positive relationship between the underlying communication skills and staff motivation with the correlation coefficient of r=0.25 and p-value = 0.042. Conclusion: Since there is a significant relationship between the underlying management communication skills (empathy, effective listening and self-efflorescence) and staff motivation, improving this dimension can increase the motivation of employees.